The Role of Belgian Airborne Sniffer Measurements in the MARPOL Annex VI Enforcement Chain - Van Roy, Ward; Merveille, Jean-Baptiste; Scheldeman, Kobe; Van Nieuwenhove, Annelore; Van Roozendael, Benjamin; Schallier, Ronny; Maes, Frank (Atmosphere, 2023)
The Royal Belgian Institute of Natural Sciences launched its airborne sniffer program in 2015 whereby a custom-built sniffer sensor was installed onboard the Belgian coastguard aircraft enabling the measurement of SO2 and NOx emitted by ocean-going vessels (OGVs). The data gathered on non-compliant OGVs were subsequently sent to port inspection authorities, who were then able to trigger inspections more rapidly than had they not had the data from the aircraft. This study reveals the added value of airborne alerts on port inspection effectiveness, a subject that had not been previously documented. This article demonstrates that airborne alerts have not only led to increased sanctions but have also drastically improved the efficiency of port inspection authorities, leading to a 50% reduction in the enforcement cost per confirmed violation. Port inspection authorities were able to follow up on 46% of the generated Fuel Sulphur Content (FSC) alerts. Of the alerts that were followed up, 43% were confirmed as non-compliant after inspection. This means that 20% of the total number of generated airborne alerts, which includes those that were not able to be followed up, met conditions for legal sanctioning. In contrast, for NOx alerts, only limited follow-ups were conducted by port inspection authorities. None of the alerts were confirmed with those inspections, mainly due to the lack of inspection mechanisms for real-world NOx emissions under IMO and EU regulations. In addition, for this study, a large-scale remote FSC measurement validation analysis was conducted for the first time, comparing airborne FSC measurements and FSC reference data. In order to obtain FSC reference data, onboard measurements from exhaust gas cleaning systems (EGCSs) were collected, together with fuel samples from Belgian port inspection authorities. The validation analysis revealed that the empiric deviation in the airborne FSC measurements with the FSC reference data was 9%, which was significantly lower than the 25% uncertainty used in the reporting of the alerts. This study helps pave the way for an increased role of airborne monitoring in the MARPOL Annex VI enforcement chain.